Effects of Mindfulness Training on School Teachers' Self-Reported Personality Traits As Well As Stress and Burnout Levels. Issue 3 (June 2020) - Fabbro, Anastasia; Fabbro, Franco; Capurso, Viviana; D'Antoni, Fabio; Crescentini, Cristiano
Among a sample of only female school teachers, we compared a mindfulness meditation (MM) training group ( n = 19) with a waiting-list control group ( n = 20) on several participant-completed questionnaires: the Five Facet Mindfulness Questionnaire, the Big Five Personality Inventory, the Teacher Stress Inventory, and the Maslach Burnout Inventory. With these measures, we assessed the participants' dispositional mindfulness, personality styles, and their stress and burnout. Following mindfulness training, teachers in the MM group showed higher trait mindfulness and conscientiousness and lower neuroticism and stress and burnout levels than teachers in the waiting-list control group. These results support the beneficial role of MM in individuals' effective management of stressful conditions in the workplace.